Acromegaly in the elderly patient - Jallad,Raquel S. (2019)
ABSTRACT Acromegaly is an insidious disease, usually resulting from growth hormone hypersecretion by a pituitary adenoma. It is most often diagnosed during the 3rd to 4th decade of life. However, recent studies have shown an increase in the incidence and prevalence of acromegaly in the elderly, probably due to increasing life expectancy. As in the younger population with acromegaly, there is a delay in diagnosis, aggravated by the similarities of the aging process with some of the characteristics of the disease. As can be expected elderly patients with acromegaly have a higher prevalence of comorbidities than younger ones. The diagnostic criteria are the same as for younger patients. Surgical treatment of the pituitary adenoma is the primary therapy of choice unless contraindicated. Somatostatin receptor ligands are generally effective as both primary and postoperative treatment. The prognosis correlates inversely with the patient’s age, disease duration and last GH level. Arch Endocrinol Metab. 2019;63(6):638-45